Efektivitas Model Project Based Learning (PjBL) Berbasis Proyek Daur Ulang dalam Meningkatkan Pemahaman Konsep IPAS Siswa Kelas V - Inni Rahmieni Nabila; Mahmud My; Paujan Azim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ conceptual understanding in Natural and Social Sciences (IPAS) among fifth-grade students at MIS Al-Mukhlisin Alam Barajo, Jambi City, particularly on the topic of water pollution. This issue was caused by teacher-centered instruction, which limited students’ opportunities to engage in meaningful and contextual learning experiences. This study aimed to examine the effect of implementing the Project Based Learning (PjBL) model through a recycling project on students’ conceptual understanding of IPAS. A quantitative approach was employed using a pre-experimental One Group Pretest–Posttest Design. The study involved 33 students selected through a saturated sampling technique. Data were collected using tests, observation, interviews, and documentation, and analyzed using the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain test with SPSS software. The results showed that the mean pretest score of 60.88 increased to 86.30 in the posttest, with an improvement of 25.42 points. The Paired Sample t-Test revealed a significance value of < 0.001 < 0.05, indicating a significant difference between pretest and posttest results. Furthermore, the N-Gain score of 0.6758 was categorized as moderate with a fairly effective improvement level. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model through a recycling project has a significant and fairly effective impact on improving students’ conceptual understanding of IPAS in grade V MIS Al-Mukhlisin Alam Barajo, Jambi City.